Preparation of starch dough using damaged cassava starch induced by mechanical activation to develop staple foods: Application in crackers. (15th January 2019) - Liu, Rong; Sun, Weidong; Zhang, Yanjuan; Huang, Zuqiang; Hu, Huayu; Zhao, Mengyao
Highlights: Damaged cassava starch (DCS) was prepared by mechanical activation. Model dough based on the pure DCS could form with appropriate damage level. Most of texture properties of DCS dough were close to that of wheat flour dough. Desired crackers were successfully prepared with DCS at the damage level of 15.37%. Application of DCS in developing staple foods based on the model dough was promising. Abstract: This study focused on evaluating the feasibility of using damaged cassava starch (DCS) to exploit staple foods. Cassava starch was subjected to damage induced by mechanical activation to obtain DCS with various degrees of damage. The increase in damage level of cassava starch led to a slight increase in amylose content and reduction in crystallinity. Damage level exerted a major influence on the pasting properties and interaction between DCS and water. SEM analysis showed that DCS tended to cohere together to form a unique dough structure in the presence of water when damage level was not less than 11.51%. Texture properties of the starch dough with damage levels of 11.51% and 15.37% were similar with those of wheat flour dough. Cracker made of DCS had acceptable sensory qualities comparable to the wheat flour counterpart. These findings confirmed that using DCS for the development of staple foods by the starch dough was practicable.